Changing Landscape for Peritoneal Dialysis: Optimizing Utilization. Issue 2 (1st February 2017) - Schreiber, Martin J.
Abstract: The future growth of peritoneal dialysis (PD) will be directly linked to the shift in US healthcare to a value‐based payment model due to PD's lower yearly cost, early survival advantage over in‐center hemodialysis, and improved quality of life for patients treating their kidney disease in the home. Under this model, nephrology practices will need an increased focus on managing the transition from chronic kidney disease to end‐stage renal disease (ESRD), providing patient education with the aim of accomplishing modality selection and access placement ahead of dialysis initiation. Physicians must expand their knowledge base in home therapies and work toward increased technique survival through implementation of specific practice initiatives that highlight PD catheter placement success, preservation of residual renal function, consideration of incremental PD, and competence in urgent start PD. Avoidance of both early and late PD technique failures is also critical to PD program growth. Large dialysis organizations must continue to measure and improve quality metrics for PD, expand their focus beyond the sole provision of PD to holistic patient care, and initiate programs to reduce PD hospitalization rates and encourage physicians to consider the benefits of PD as an initial modality for appropriate patients. New and innovative strategies are needed to address the main reasons for PD technique failure, improve the connectivity of the patient in the home, leverage home biometric data to improve overall outcomes, and develop PD cycler devices that lower patient treatment burden and reduce both treatment fatigue and treatment‐dependent complications.